The global and regional in China's nation-formation [ - Duara, Prasenjit (Critical Asian scholarship, 2009)
The author covers the major historical problems of China in the 20th century, namely imperialism, nationalism, state-building, religion and the role of history from the perspective of global and regional circulations and interactions